TPACK Approach to Improving HOTS in Arabic Language Learning: Strategies and Challenges - Ahmadi, Yondri; Waluati Triana, Hetti; Ritonga, Mahyudin (Shaut al Arabiyyah, 2024)
This article discusses the role of Arabic language teaching in the development of students' Higher Order Thinking Skills (HOTS), identifying challenges in conventional approaches which tend to focus on basic aspects and lack connection with HOTS development. The article offers a solution by implementing the TPACK (Technological Pedagogical Content Knowledge) approach, enabling the integration of technology in Arabic language learning. Implementing TPACK can help teachers become more effective in teaching and stimulate students to think creatively, analyze information, and make wise decisions. The research method uses a qualitative approach with case studies, involving interviews, observation and documentation in Arabic language learning. The results of the analysis using the Miles & Huberman model illustrate the challenges in implementing TPACK and HOTS, such as changes in technology, access, and curriculum adjustments, but provide benefits, such as learning variety, focus on students, and increasing the quality of technology use. The article also highlights the opportunities and challenges of digital-based Arabic language learning, with the important role of teachers, students and learning devices in implementing HOTS. Overall, the article on the importance of TPACK and the development of HOTS in Arabic language learning, offers innovative strategies to increase learning effectiveness and students' higher-order thinking abilities. The challenges of the 21st century are also a concern for educators today, that future students will be more technologically literate.